Number preferences in lotteries - Wang, Tong V.; Potter van Loon, Rogjer J.D.; van den Assem, Martijn J.; van Dolder, Dennie (European Association for Decision Making, 2016)
We explore people's preferences for numbers in large proprietary data sets from two different lottery games. We find that choice is far from uniform, and exhibits some familiar and some new tendencies and biases. Players favor personally meaningful and situationally available numbers, and are attracted towards numbers in the center of the choice form. Frequent players avoid winning numbers from recent draws, whereas infrequent players chase these. Combinations of numbers are formed with an eye for aesthetics, and players tend to spread their numbers relatively evenly across the possible range.